Nilai Pendidikan Karakter Peserta Didik dalam Pembelajaran Ilmu Pengetahuan Sosial di Sekolah Dasar - Hidayah, Noor; Febrianti, Sindy; Virgianti, Nanda Enita; Jadidah , Ines Tasya (Indo-MathEdu Intellectuals Journal, 2023)
This research is related to the Character Education Values of Students in Social Science Learning at Elementary Schools. It is literature review research. Data collection in this study is conducted through a review based on several references, including journal articles, documents, and various teaching materials. The data collection process involves searching for sources and constructing information from various sources, such as books, journals, and previous research. The literature obtained from various references is critically and comprehensively analyzed with the aim of supporting the proposed propositions and ideas. Character education is based on the psychological totality involving all human potential (cognitive, affective, psychomotor). Through social science learning, character education values can be incorporated by integrating them into the content of social science lessons.